Investigating dependencies between laser drilling process parameters, recast layer thickness and corrosion-fatigue life for turbine vane cooling film holes. - Morar, Nicolau Iralal (Cranfield University, 2017)
Manufacturers of aeroengines are currently being confronted with service related degradation process such as fatigue, thermal fatigue, creep, hot corrosion, wear, corrosion-fatigue and fretting. These degradation modes are causing engine operational disruption, unscheduled maintenance burden, and costly components replacement. Degradation of components and systems is a continuous process that results in loss of function and performance when exposed to fluctuating loads and an adverse operating environment. Understanding of factors and drivers influencing premature degradation and early damage on critical aeroengine mechanical components is needed. As such, the purpose of the present research was to develop an understanding of the impact of manufacturing process and parameters used on the corrosion-fatigue life of an aeroengine turbine vane based on the past degradation information. Based on the service experience data, turbine vane cooling film holes shown to be life limiting feature, which are exposed to high cyclic stresses and temperatures in harsh environment. Therefore, understanding of fatigue life degradation of turbine vane cooling holes and impact of drilling method and environment provides an insight and knowledge for the changes in effusion cooling holes design and/or optimisation of drilling parameters. The research has been able to establish the effects of key laser drilling process parameters, such as the influence of peak power, pulse frequency and trepan speed on the recast layer thickness and surface cracks formation in a Ni-base CMSX-4 superalloy angled cooling holes. The results indicate that trepan speed and peak power had significant influence on the thickness of the recast layer and cracks formation around the sidewalls of cooling holes, both statistically and physically. The metallography examinations show that the recast layer has an altered morphology. Furthermore, elemental analysis and nano indentations measurements on the recast layer show that there is change in alloy chemistry and mechanical properties, respectively. Therefore, less resistant to fatigue crack initiation and corrosion than base alloy. The high temperature corrosion-fatigue of critical components and features such as laser drilled cooling holes has received very little attention. The occurrence of high temperature corrosion is associated with an accelerated oxidation and sulphidation assisted cracking, driven by salt and sulphur concentration. In high temperature corrosion, formation of thick oxide scale and micro pits in the recast and alloy surface leads to potential early onset of fatigue crack initiation and accelerated crack advance on the pre-existing cracks. Therefore, impacting the life performance of laser drilled components. As such, research into interaction between laser drilling, recast layer thicknesses and high temperature corrosion-fatigue life has been undertaken. The representative laser drilled cooling holes specimens were tested in laboratory with different range of recast layer thickness and representative of service conditions. The corrosion-fatigue in CMSX-4 bare specimens found to give life debit between 20 to 25% from the air fatigue data. Corrosion-fatigue tests result show that laser drilled fatigue specimens provide a fatigue life debit between 30 to 40% from un-drilled specimens tested under similar conditions. The recast layer thickness had significant influence of the corrosion-fatigue strength degradation of cooling holes, particularly in crack nucleation. The role of environment was also significantly in both crack nucleation and short crack growth. The research work developed in this thesis contributes to the understanding of the role of laser drilling process parameters and recast layer thickness interaction and their effects on the corrosion-fatigue life and surface crack initiation in cooling holes, and how empirical methods can be used to extend the lives of turbine vane cooling film holes.
Keywords: Degradation analysis; corrosion-fatigue; turbine vanes; CMSX-4; laser trepan drilling; cooling film holes; recast layer; surface cracks